58.7k views
0 votes
Simplify (6m2-5m+4)+(7m2+2m-5)

User J Brazier
by
4.5k points

2 Answers

5 votes

Answer:13m2 - 3m - 1 i think that is the answer


Explanation:


User Andreas Gohr
by
4.6k points
2 votes

Answer:

44m^2 - 23m^3 - 12m^2 + 33m - 20

Explanation:

To get this answer, you'll need to multiply the two expressions together. There are two methods to do this - the box method and FOIL.

Using the box method, you'll set up a three by three box in which the top is lined with the first equation and the left is lined with the second.

Each box will now have a corresponding number - for instance, the corner most box with the number 6m^2 on top and 7m^2 to the left will be multiplied by each other to produce 42m^4.

The exponent changed as when two exponents are multiplied together, they are added.

These are all the combinations you should need to multiply are listed below as well as their products:

6m^2 x 7m^2 = 42m^4

-5m x 7m^2 = -35m^3

4 x 7m^2 = 28m^2

6m^2 x 2m = 12m^3

6m^2 x -5 = -30m^2

-5m x 2m = -10m^2

4 x 2m = 8m

4 x - 5 = -20

-5m x -5 = 25m

Add together the like terms (have to have same variable AND exponent)

42m^4 and -20 have no like terms.

-35m^3 + 12m^3 are like terms that produce = -23m^3

28m^3 + -30m^2 + -10m^2 = -12m^2

25m + 8m = 33m

When putting together the simplified equation, make sure to have them in order from largest to smallest exponent.

Hope this helps!



User Wchargin
by
6.3k points